Recovery of palladium from a spent automobile catalyst leaching solution by a thiodiglycolamide derivative - Paiva, A. P. (2016)
In the sequence of previous research on the development of novel liquid-liquid amidetype compounds to efficiently and selectively extract platinum-group metals (PGMs) from concentrated hydrochloric acid media, a specific thiodiglycolamide derivative – N,N’-dimethyl-N,N’-dicyclohexylthiodiglycolamide (DMDCHTDGA) – has been applied for the recovery of palladium(II) from a spent automobile catalyst leaching solution, containing palladium(II) and rhodium(III) as PGMs. The results obtained are rather promising, since the DMDCHTDGA behavior towards the two PGMs is similar to that observed for hydrochloric acid aqueous media studied before, simulating the real leaching phases. Within eleven metal elements co-existing in solution, the majority in high fold-excesses, only aluminum(III) and cerium(III) interfere in the palladium(II) liquid-liquid extraction process, requiring further optimization.